1992
DOI: 10.1002/ddr.430260308
|View full text |Cite
|
Sign up to set email alerts
|

Mianserin‐induced 5‐HT2 receptor downregulation results in anxiolytic effects in the elevated plus‐maze test

Abstract: Benjamin, D., E.I. Saiff, T. Nevins, and H. Lal: Mianserin-induced 5-HT2 receptor downregulation results in anxiolytic effects in the elevated plus-maze test. Drug Dev. Res. 26~287-297, 1992. Several agents that downregulate 5-Hl-2 receptors produce anxiolytic effects in humans, but the role of 5-HT2 receptor downregulation has been difficult to assess because of their other actions. To test the effects of pharmacological downregulation of 5-HT2 receptors on exploratory behavior in the mouse, mianserin, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A potential mechanism for the delayed onset of effect is provided by the report that binding of selective ligands to 5-HT 2A and 5-HT 2C receptors were significantly reduced 48 h after pretreatment with mianserin [Benjamin et al, 1992]. Binding to 5-HT 1A , 5-HT 1B , and β-adrenergic receptors were not effected.…”
Section: Monoaminergic Sites Serotonergic Receptorsmentioning
confidence: 93%
See 1 more Smart Citation
“…A potential mechanism for the delayed onset of effect is provided by the report that binding of selective ligands to 5-HT 2A and 5-HT 2C receptors were significantly reduced 48 h after pretreatment with mianserin [Benjamin et al, 1992]. Binding to 5-HT 1A , 5-HT 1B , and β-adrenergic receptors were not effected.…”
Section: Monoaminergic Sites Serotonergic Receptorsmentioning
confidence: 93%
“…5-HT 2 antagonists have been found to reverse anxiety-like behaviors in the EPM during EW. Single doses of mianserin, a 5-HT 2 antagonist, given either 2 or 7 days before cessation of ethanol, blocked the development of anxiogenic signs in the EPM during EW [Benjamin et al, 1992;Lal et al, 1993;Prather et al, 1991b]. Little effect was seen at 15 min after administration of mianserin.…”
Section: Monoaminergic Sites Serotonergic Receptorsmentioning
confidence: 94%
“…Also, the anxiolytic effects of 5-HT2 antagonists can be overcome by agonists of these receptors. In addition, it has been suggested that 5-HT2 receptors may play an inhibitory role on plus-maze behavior and that a down-regulation of these receptors may be responsible for the anxiolytic profile observed 48 h after mianserin administration (Benjamin et al 1992). Thus, a different explanation for the mechanism of action could be offered.…”
Section: Discussionmentioning
confidence: 99%